2020
DOI: 10.1017/wet.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of herbicide efficacy and application timing for giant miscanthus (Miscanthus x giganteus) biomass reduction

Abstract: Giant miscanthus has the potential to move beyond cultivated fields and invade noncrop areas, but this can be overshadowed by aesthetic appeal and monetary value as a biofuel crop. Most research on giant miscanthus has focused on herbicide tolerance for establishment and production rather than terminating an existing stand. This study was conducted to evaluate herbicide options for control or terminating a stand of giant miscanthus. In 2013 and 2014, field experiments were conducted on established stands of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Finally, integrated control techniques should be investigated for control of M. × giganteus , as mechanical and biological control methods have been reported to reduce M. × giganteus growth (Barksdale 2016; Barney et al 2012). Barney et al (2012) reported damage to M. × giganteus by an unknown herbivore in lowland riparian habitats to such an extent that it precluded long-term growth assessment, suggesting that herbivory/grazing alone or as part of an integrated management strategy warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, integrated control techniques should be investigated for control of M. × giganteus , as mechanical and biological control methods have been reported to reduce M. × giganteus growth (Barksdale 2016; Barney et al 2012). Barney et al (2012) reported damage to M. × giganteus by an unknown herbivore in lowland riparian habitats to such an extent that it precluded long-term growth assessment, suggesting that herbivory/grazing alone or as part of an integrated management strategy warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Barney et al (2012) reported damage to M. × giganteus by an unknown herbivore in lowland riparian habitats to such an extent that it precluded long-term growth assessment, suggesting that herbivory/grazing alone or as part of an integrated management strategy warrants further investigation. Simulated mowing reduced M. × giganteus rhizome production and biomass 59% to 71% at 13 WAT in a greenhouse experiment while increasing shoot density (34%) and aboveground biomass (83%), suggesting that treated plants utilized rhizome starch reserves to increase aboveground growth as a recovery mechanism after mowing (Barksdale 2016). Repeated clipping of aboveground biomass of other perennial rhizomatous plant species has been shown to be a potential control mechanism if clipping is conducted frequently enough to repeatedly reduce plant biomass (Derr 2008; Turnage et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations